2014
DOI: 10.1177/039463201402700312
|View full text |Cite
|
Sign up to set email alerts
|

Do Elevated Serum IgM Levels Have to Be Included in Probable Diagnosis Criteria of Patients with Ataxia-Telangiectasia?

Abstract: Ataxia-telangiectasia (AT) is a rare multisystem, neurodegenerative genetic disorder that is characterised by progressive neurological abnormalities, oculocutaneous telangiectasias and immunodeficiency. Delay in diagnosis or misdiagnosis is probable due to its wide clinical heterogeneity in infancy. Recurrent sinopulmonary infections are often the only presenting symptom and usually patients have decreased immunoglobulins. A total 10% of patients who present with decreased serum immunoglobulin G and A and with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 23 publications
(37 reference statements)
1
13
0
1
Order By: Relevance
“…Hypogammaglobulinemia with low IgG, IgA and IgE levels, is a frequent presentation of this disease [ 27 ]. On the other hand, different studies have shown variability in IgM levels in these patients with normal or mildly elevated levels in up to 60% of the patients [ 19 ]. As a result, some AT patients are initially misdiagnosed with Hyper IgM syndrome, while the definitive AT diagnosis is made later by genetic analysis or western blot, following the accumulation of clinical characteristics indicative of AT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypogammaglobulinemia with low IgG, IgA and IgE levels, is a frequent presentation of this disease [ 27 ]. On the other hand, different studies have shown variability in IgM levels in these patients with normal or mildly elevated levels in up to 60% of the patients [ 19 ]. As a result, some AT patients are initially misdiagnosed with Hyper IgM syndrome, while the definitive AT diagnosis is made later by genetic analysis or western blot, following the accumulation of clinical characteristics indicative of AT.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have suggested that a subgroup of patients with AT present with higher levels of IgM that might be associated with a more severe phenotype [ 15 19 ]. A more recent study describing a cohort of 61 patients, concluded that patients with Hyper IgM phenotype and IgG2 deficiency showed decreased survival compared to AT patients with NIgM [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Diagnosis of AT patients may be delayed due to the wide variability in clinical phenotype; the syndrome is frequently confused with cerebral palsy and the immunological evaluation overlooked or misdiagnosed as Hyper-immunoglobulin M syndrome (9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…It is characterized by oculocutaneous telangiectasias, variable immunodeficiency and progressive neurological abnormalities such as uncoordinated, ataxic movements as a result of cerebellar cortical degeneration [1][2] . Other features include retardation of somatic growth, premature aging, radiosensitivity and predisposition to cancer 2 .…”
mentioning
confidence: 99%
“…Other features include retardation of somatic growth, premature aging, radiosensitivity and predisposition to cancer 2 . Definitive diagnosis is made by revealing a disease causing mutation on ATM gene which was identified in 1995 in 11q22-23, coding for a protein implicated in genomic homeostasis in case of radio-induced DNA double-strand breaks [1][2][3] .…”
mentioning
confidence: 99%